Design and Initial Characterization of a Small Near-Infrared Fluorescent Calcium Indicator - Matlashov, Mikhail E.; Vera, Jorge; Kasatkina, Ludmila A.; Khodakhah, Kamran; Verkhusha, Vladislav V. (Frontiers in Cell and Developmental Biology, 2022)
Near-infrared (NIR) genetically encoded calcium indicators (GECIs) are becoming powerful tools for neuroscience. Because of their spectral characteristics, the use of NIR GECIs helps to avoid signal loss from absorp//tion by body pigments, light-scattering, and autofluorescence in mammalian tissues. In addition, NIR GECIs do not suffer from cross-excitation artifacts when used with the most common fluorescent indicators and optogenetics actuators. Although several NIR GECIs have been developed, there is no NIR GECI currently available that would combine high brightness in cells and photostability with small size and fast response kinetics. Here we report a small FRET-based NIR fluorescent calcium indicator iGECInano. We characterize iGECInano in vitro, in non-neuronal mammalian cells, and in primary mouse neurons. iGECInano demonstrates the improvement in the signal-to-noise ratio and response kinetics compared to other NIR GECIs.